2021
DOI: 10.7717/peerj.11619
|View full text |Cite
|
Sign up to set email alerts
|

Grab what you can—an evaluation of spatial replication to decrease heterogeneity in sediment eDNA metabarcoding

Abstract: Environmental DNA methods such as metabarcoding have been suggested as possible alternatives or complements to the current practice of morphology-based diversity assessment for characterizing benthic communities in marine sediment. However, the source volume used in sediment eDNA studies is several magnitudes lower than that used in morphological identification. Here, we used data from a North Sea benthic sampling station to investigate to what extent metabarcoding data is affected by sampling bias and spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Sampling approaches and theory are understudied aspects of eDNA protocols (Dickie et al, 2018), and future work should evaluate the optimal sampling volume and strategy as a function of the environment and the biology of target taxa (Mächler et al, 2016). Studies in other environments have similarly demonstrated that increasing sample volumes can improve biodiversity detection (Bessey et al, 2020;Hestetun et al, 2021;Schabacker et al, 2020;Sepulveda et al, 2019). Because our eDNA sampler can efficiently pump a much larger volume than that which can be captured by a single Niskin bottle, it represents a better tool for collecting eDNA at deeper ocean depths (i.e., below ~100 m).…”
Section: Sampling Volumementioning
confidence: 99%
“…Sampling approaches and theory are understudied aspects of eDNA protocols (Dickie et al, 2018), and future work should evaluate the optimal sampling volume and strategy as a function of the environment and the biology of target taxa (Mächler et al, 2016). Studies in other environments have similarly demonstrated that increasing sample volumes can improve biodiversity detection (Bessey et al, 2020;Hestetun et al, 2021;Schabacker et al, 2020;Sepulveda et al, 2019). Because our eDNA sampler can efficiently pump a much larger volume than that which can be captured by a single Niskin bottle, it represents a better tool for collecting eDNA at deeper ocean depths (i.e., below ~100 m).…”
Section: Sampling Volumementioning
confidence: 99%
“…The underperformance by the 0.5‐g sample analyses may be resolvable with the collection of several (pseudo‐) replicate samples (i.e. > 2), or subsampling homogenized samples of larger volume (Hestetun, Lanzén, & Dahlgren, 2021; Hestetun, Lanzén, Skaar, & Dahlgren, 2021; van der Loos & Nijland, 2021). Currently, there is no consensus regarding the appropriate level of replication for assessment of total diversity, especially when considering effort/cost vs. benefit (e.g., review by Pawlowski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lear et al (2018) showed that the 18S gene is the most popular marker for targeting eukaryotes in metabarcoding research. 18S primers have been shown to outperform primers from other genes (von Ammon et al 2018, Sawaya et al 2019, Tytgat et al 2019, Hestetun et al 2021). The V9 subregion of the eukaryotic SSU (18S) rRNA gene - used in this research - has both highly conserved and highly variable sites, thus showing great taxonomic resolution potential (Amaral-Zettler et al 2009, Wu et al 2015).…”
Section: Discussionmentioning
confidence: 99%